Recovery - the magic ingredient of any training program - Hamilton, A.; Lawson, T.; Marshall, J.; Grantham, N.; Fletcher, E. (Peak Performance, 2007)
SECTION I - NUTRITION AND RECOVERY Eating and recovery: should protein replenishment start before exercise? (Andrew Hamilton) Milk and recovery - what`s the story? (Amanda Carlson) Halftime recovery - what`s best for maximising fulltime performance? Tim Lawson The glycaemic index: how to use it for optimum recovery`(Andrew Hamilton) Could GABA be a magic bullet for recovery? (Andrew Hamilton)